Question
upstudy study bank question image url

1 Which expression ifequivalent to \( 10 k+17-7 j=10-11 k ? \) \( 0-8, k=1 \) \( 0-7 j=k-1 \) \( 0-7 j+k+1 \) \( 0-8 j-k \)

Ask by Young Robbins. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

None of the given expressions are equivalent to the original equation.

Solution

Solve the equation by following steps: - step0: Solve for \(j\): \(10k+17-7j=10-11k\) - step1: Move the expression to the right side: \(-7j=10-11k-\left(10k+17\right)\) - step2: Subtract the terms: \(-7j=-7-21k\) - step3: Change the signs: \(7j=7+21k\) - step4: Divide both sides: \(\frac{7j}{7}=\frac{7+21k}{7}\) - step5: Divide the numbers: \(j=1+3k\) To find an expression equivalent to \( 10k + 17 - 7j = 10 - 11k \), we first solve for \( j \). 1. Rearranging the equation: \[ 10k + 17 - 7j = 10 - 11k \] 2. Move all terms involving \( j \) to one side and the rest to the other side: \[ -7j = 10 - 11k - 10k - 17 \] Simplifying the right side: \[ -7j = -21k - 7 \] 3. Dividing both sides by -7: \[ j = 3k + 1 \] Now, we can express \( j \) in terms of \( k \) as \( j = 3k + 1 \). Next, we will check which of the given expressions is equivalent to this result: 1. **Expression 1:** \( 0 - 8, k = 1 \) - This does not relate to \( j \). 2. **Expression 2:** \( 0 - 7j = k - 1 \) - Rearranging gives \( 7j = 1 - k \), or \( j = \frac{1 - k}{7} \), which is not equivalent. 3. **Expression 3:** \( 0 - 7j + k + 1 \) - Rearranging gives \( 7j = k + 1 \), or \( j = \frac{k + 1}{7} \), which is not equivalent. 4. **Expression 4:** \( 0 - 8j - k \) - Rearranging gives \( 8j = -k \), or \( j = -\frac{k}{8} \), which is not equivalent. None of the provided expressions are equivalent to \( j = 3k + 1 \). Thus, the answer is that none of the expressions are equivalent to the original equation.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find an expression equivalent to \( 10k + 17 - 7j = 10 - 11k \), we'll rearrange the equation. First, we can move all terms involving \( k \) to one side and everything else to the other side. Rearranging gives us \( 10k + 11k = 10 - 17 + 7j \), simplifying to \( 21k = -7 + 7j \). Dividing everything by 7 gives us \( 3k = j - 1 \). From this, we can derive that \( 0 - 7j + k + 1 = 0 \), which correlates to the expression \( 0-7 j+k+1 \). So the correct answer is \( 0 - 7 j + k + 1 \). Now, let's dive into some relevant insights: Did you know that equations like this one can represent lines in a graph? The variables \( k \) and \( j \) can be thought of as coordinates in a 2D plane! Solving the equation helps you visualize relationships between these variables—it's like drawing a treasure map where each point gives you clues to find arcs of relationships! When manipulating equations like this, a common mistake is forgetting to correctly distribute or combine like terms. Always double-check your algebra! A misstep while simplifying can lead to answers that seem right but ultimately lead you down the wrong path. Keep your work organized, and it becomes much easier to catch those pesky errors!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy